Verzuiling, pacificatie en kentering in de Nederlandse politiek (De Bussy, 1979)
Bew. door A. Lijphart van The politics of accomodation : pluralism and democracy in the Netherlands. Berkeley : University of Californ is Press, 1968. - Bibl., index.